Increasing The Success Of The Go No Sen Strategy In Kumite Athletes In Karate With Life Kinetik Exercises - Seda, Anthony Paramadina; Komarudin; Nida'ul Hidayah (Universitas Negeri Jakarta, 2025)
The go no sen strategy is one of the techniques in kumite karate, which is by retaliating against the opponent's attack. This technique is done by avoiding or fending off the opponent's attack, then immediately counterattacking. The purpose of this study is to scientifically research the application of Life Kinetik training to increase the success of the go no sen strategy in kumite athletes. The research uses an experimental approach with a quasi-experimental method. A total of 30 Karate UKM athletes from the University of Education Indonesia were the population in this study and as many as 18 kumite athletes were sampled in this study. This study uses a Non equivalent Control Group Design. The data from the study was analyzed using the Wilcoxon Signed Rank Test. The results of the control group obtained a significance value of 0.564 (greater than 0.05) which means that there was no significant improvement between the pretest and post-test. Meanwhile, in the treatment group, a significance value of 0.007 (less than 0.05) was obtained, which means that there was a significant increase in Life Kinetik training on the success of the go no cent strategy in kumite athletes. The conclusion is that Life Kinetik training can increase the success of the go no sen strategy in kumite athletes.